Playing Number Wheel to Improve Early Numeracy Skill Action Research in Bon Thorif Kindergarten - Murodi, Sri Sumarni; Andika, Windi Dwi (Universitas Negeri Semarang, 2018)
Pupils’ low early numeracy skill was found as a problem in a preliminary study with average percentage 52,05% based on observation and attitude test. This was resulted from paper and pencil activities involving drilling in the instruction. The researchers, therefore, offered direct solution for increasing early numeracy skill of kindergarten pupils B by playing Number Wheel at Kindergarten Bon Thorif located in Palembang South Sumatera, Indonesia. Number Wheel was media of pointing numbers modified from Charlesworth’s media (2000, p.104). This media was in the shape of circle with 10 numbers from number 1 to 10 with different colours on its surface. This circle could spin at its center like a wheel and stop exactly on the clock hand pointing numbers. The method used classroom action research. The subjects were 13 pupils, 6 years old. Data collection techniques were test and non test. The data obtained from observation were gathered from field-notes and photographs. Data regarding an early numeracy skill were gathered by using an attitude test and observation. The indicator of the success of this research was shown by the improvement up to 71% for each pupil. The data analysis indicated that there was improvement 78,56% of pupils’ early numeracy skill in the frist cycle and 99,45% in the second cycle. This proved that the improvement was significant. The implication is that playing Number Wheel can be an alternative way to increase kindegarten pupils’ early numeracy skill. Future study is suggested to develop more innovative media to improve early numeracy skill.